Analisis Kerusakan Pada Struktur Bangunan Akibat Beban Melebihi Kapasitas - cindy Novigu Dalow buulolo (CV. SINAR HOWUHOWU, 2026)
Damage to building structures is a common problem in the construction industry and has the potential to significantly impact the safety of building users. One of the main factors causing structural damage is loads exceeding the building's design capacity. These overloads can arise from changes in building function, the addition of structural elements, and the building owner's lack of understanding of the structure's capacity limits. This study aims to analyze the forms of damage to building structures due to overloading and their causal factors through a qualitative approach. The methods used include literature review, indirect observation through case documentation, and descriptive analysis of the phenomenon of building structural damage. The study results indicate that overloading can cause various types of damage, including structural cracks, excessive deflection, foundation settlement, and structural failure. Therefore, careful structural evaluation and supervision are necessary to prevent building damage due to overloading.